Modelling the Demand for Imports and Domestic Output - Bjørn E. Naug (Statistics Norway, Research Department, 1999)
The paper models domestic output over imports in Norway's expenditure on manufactures. Using Johansen's (1988, 1991) method, we obtain a cointegrating vector between the output-imports ratio, relative prices and a proxy for international specialisation. This vector enters a conditional equilibrium correction model of the output-imports ratio; a model which also includes short-run influences of relative prices and a negative coefficient for domestic capacity utilisation. The utilisation coefficient aside, we do not find significant activity effects on the output-imports ratio. Lastly, the model passes several tests of the Lucas critique.
Keywords: C22; C32; F12; F14; 330; Import share; international specialisation; cointegration; Johansen procedure; equilibrium correction model; parameter constancy; Lucas critique.